Pengaruh Program Keselamatan Dan Kesehatan Kerja, Beban Kerja Terhadap Kinerja Karyawan Yang Dimediasi oleh Stress-Kerja pada Mitra Pengguna Jasa Layanan Balai Keselamatan dan Kesehatan Kerja Medan - Indria Primiaty Diningsih; Leylia Khairani; Hazmanan Khair (Jurnal AKMAMI (Akuntansi Manajemen Ekonomi), 2021)
This study aims to determine the effect of occupational safety and health programs (K3) and workloads on employee performance mediated by work stress on service user partners of Balai K3 Medan. The research method used is quantitative research, where variables are measured using a likert scale. The number of samples in this study was 70 people who became partners of balai K3 Medan service users. The data collection techniques used in this study are document studies, questionnaires and interviews. Data analysis techniques using Structural Equational Modeling (SEM) using Smart–PLS. The results showed that: (1) The K3 Program negatively and significantly affects employee performance, workload and work stress positively and significantly affect employee performance, (2) the K3 Program has a negative but insignificant effect, and the workload positively and significantly affects employee performance and positively affects work stress, (3) Workload mediated by work stress has a significant effect, and (4) the work stress-mediated K3 Program has no significant effect on employee performance.